Strategi Yayasan Dalam Mencapai Kemandirian Keuangan Panti Asuhan NU An-Nuur Kota Kediri - Siska Yulia Weny (Journal of Islamic Education Management, 2022)
The situation of financial surplus at the NU An-Nuur Orphanage in Kediri City in the last 4 years regarding the financial independence strategy implemented so that the manager can fund the needs of the orphanage without prioritizing donation funds. This study aims to determine the foundation's strategy in achieving financial independence at the NU An-Nuur Orphanage, Kediri City. The method used is qualitative, taking the background at the NU An-Nuur Orphanage, Kediri City. Data were collected through interviews, observation, and documentation. The data analysis stage begins with data collection, data reduction, data presentation, and data conclusion or data verification. The validity of the data is done by triangulation. The results of this study indicate that the NU An-Nur Orphanage in Kediri City can be said to be financially independent. The orphanage has several types of organizational independence, namely learning independence, socialization independence, and financial independence. In achieving financial independence, the orphanage implements a number of strategies, implements an independent financial management system, fosters the entrepreneurial spirit of foster children, determines priority sources of income and fosters the spirit of sharing with others in foster children, conducts several businesses, including renting a rented house, boarding house for girls, shops, catering. , livestock business, cloth bags, rental of transportation equipment and cooperation partnerships with Telkomsel. Then for some of the obstacles experienced by the orphanage in managing its business business, the bookkeeping of business results is not adequate, fear of the risk of loss to the business, limited human resources and product marketing strategies have not been maximized.